LAYANAN BIMBINGAN KELOMPOK SECARA DARING MELALUI TEKNIK DISKUSI KELOMPOK UNTUK MINAT BELAJAR SISWA KELAS VII SMPN 2 PURWAKARTA - Elyta Yustika Machmud; Heris Hendriana; Tuti Alawiyah (IKIP Siliwangi, 2023)
This study is based on the impact of the COVID-19 pandemic on implementation of Guidance and Counseling services in schools. Group guidance services given to students who have low learning interest problems. To assist online group guidance services, group discussion techniques are needed. This study used a qualitative research method. The data collection used was observation, interviews, and documentation. The subjects of this study were amount 5 students who had problems with low interest in learning. As a results obtained after providing online group guidance service using the group discussion technique there are changes in students. Based on research that online group tutoring services through group discussion techniques are effective in increasing the learning interest of class VII students of SMPN 2 Purwakarta. Keywords:Interest in Learning, Techniques of Group Discussions, Group counseling online